Geologic reconnaissance map of the southern part of Seward Peninsula / U.S. Geological Survey - Geological Survey (U.S.) (Washington, D.C. : Geological Survey (U.S.), 1907)
Relief shown by contours and spot heights. Surveyed under the direction of Alfred H. Brooks, 1900-1906. Upper right corner of map missing. Color 1:250,000